Development of economic processes utilizing solar energy - Kumar Kalyan (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2022)
Abstract. The concern of the electric utility companies to prioritize tight control on system performance is addressed in the paper as it immensely helps planning maintenance expenditure economically with customers’ expectations fully met. The paper aims at making a comparative study of performance of the micro-grid power system with that of the interconnected micro-grid and national grid. A micro-grid that utilizes solar energy in sparse locations in hilly terrain for ensuring reliable electric supply to industrial houses engaged in product manufacturing processes has been considered. These manufacturing processes as a part of small and medium industries introduce goods and services necessary for securing economic growth and development in the country side where grid power supply is subject to frequent weather disturbances, and hence, very costly from the perspective of sustenance as well as maintenance. The solar energy trend has given scope for self-reliance and better livelihood of people who live away from cities but the products what they manufacture may be sent for consumption in the nearby cities. Thus, more and more dependence on the solar energy leads to nation’s economic growth policy. Moreover, it adds to uninterrupted and quality electric supply using clean energy in place of fossil fuels-based generation of electricity to protect environment; allows reducing health hazards and mitigating greenhouse gas emissions. Using reliability techniques, solar energy plant performance is quantitatively judged and compared with respect to the performance of the national grid supplying power supply to the remotely located population. The improved energy security, easy access and operational responses of the solar plant as a substitute to the grid power supply help develop economic growth of a nation.

A cikk azt vizsgálja, hogy az áramszolgáltató cégek számára milyen problémát jelent a rendszerteljesítmény szigorú ellenőrzésének előtérbe helyezése, mivel ez nagyban segíti a karbantartási költségek gazdaságos tervezését a vevői elvárások egyidejű kielégítésével. A tanulmány célja a mikrohálózat teljesítményének összehasonlító elemzése az egységes mikrohálózattal, valamint az országos villamosenergia-hálózat teljesítményével. Olyan mikrohálózatot vizsgáltunk, mely dombos területen elhelyezkedő napenergiát használ a termékgyártási folyamatokkal foglalkozó ipari épületek megbízható áramellátásához. Ezek a termelési folyamatok mint a kis- és közepesnagyságú ipar részeként olyan árukat és szolgáltatásokat vezetnek be, amelyek egy országban a gazdasági növekedés és fejlődés biztosításához szükségesek, és ahol a hálózati energiaellátás időjárási viszonyoknak van kitéve, s ezért nagyon költséges a fenntartás és a karbantartás szempontjából. A napenergia felhasználásának trendje teret adott a városoktól távol élő emberek önellátásához és jobb megélhetéséhez, de az általuk előállított termékek a környező városok fogyasztóihoz is kerülhetnek. Így a napenergiától való növekvő függőség az ország gazdasági növekedési politikájához vezet. Emellett a fosszilis tüzelőanyag alapú villamosenergia-termelés helyett tiszta energiát használó, zavartalan és jó minőségű villamosenergia-ellátást segít elő a környezetvédelem érdekében, ami csökkenti az üvegházhatású gázok kibocsátását és ennek megfelelően az egészségügyi kockázatokat is. Megbízhatósági vizsgálati módszerek segítségével egy naperőmű teljesítményét számszerűsítik és összehasonlítják a távolabban élő lakosságot ellátó országos villamoshálózat teljesítményével. A jobb energiabiztonság, a könnyű hozzáférés és a napenergia rugalmassága, mint a központi hálózati rendszer helyettesítője, elősegíti az ország gazdasági növekedését.

Резюме. У статті розглядається проблема електропостачальних компаній щодо встановлення пріоритету жорсткого контролю за продуктивністю системи, оскільки це надзвичайно допомагає економно планувати витрати на технічне обслуговування з повним задоволенням очікувань клієнтів. Метою дослідження є проведення порівняльного аналізу продуктивності мікромережі з продуктивністю об’єднаної мікромережі та національної електромережі. Досліджено мікромережу, яка використовує сонячну енергію в розріджених місцях на горбистій місцевості для забезпечення надійного електропостачання промислових будинків, які займаються процесами виробництва продукції. Ці виробничі процеси, як частина малих і середніх галузей промисловості, впроваджують товари та послуги, необхідні для забезпечення економічного зростання та розвитку в країні, де мережеве електропостачання зазнає частих погодних умов і, отже, є дуже дорогим з точки зору існування, а також обслуговування. Тенденція використання сонячної енергії дала простір для самозабезпечення та кращих засобів до існування для людей, які живуть далеко від міст, але продукти, які вони виробляють, можуть відправлятися для споживання в сусідні міста. Таким чином, все більша залежність від сонячної енергії призводить до політики економічного зростання країни. Крім того, це сприяє безперебійному та якісному електропостачанню з використанням чистої енергії замість виробництва електроенергії на основі викопного палива для захисту навколишнього середовища, що зменшує викиди парникових газів та відповідно ризики для здоров'я. За допомогою методів перевірки надійності продуктивність сонячної електростанції кількісно оцінюється та порівнюється з продуктивністю національної мережі, що постачає електроенергію віддаленому населенню. Покращена енергетична безпека, легкий доступ і оперативні реакції сонячної електростанції як заміни електромережі допомагають розвивати економічне зростання країни.
A napenergia felhasználásával kapcsolatos gazdasági folyamatok fejlődése
Розвиток економічних процесів, пов'язаних з використанням сонячної енергії
https://aab-economics.kmf.uz.ua/aabe
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00010508
Keywords: Solar energy; Micro-grid; Capacity; Loss of load; Reliability indices; Risk